The Effect of Online Review on Online Purchase Intention - Mishra, Udgam (Researcher: A Research Journal of Culture and Society, 2021)
The primary goal of this research is to examine the effect of online reviews on online purchase intention. The study investigates the influence of review valence, review relevance and review accuracy on the online purchase intention. Cross-sectional data were collected using a self-administered questionnaire from 251 Nepalese from the eastern part. The data were then analyzed using structural equation modeling. Amos 21 was used to analyze the gathered data. The findings reveal that review accuracy has a favorable and significant impact on online purchase intention. Whereas, review valence and review relevance on other hand have no substantial impact on online purchase intention. The work founded on prior research basing review valence, review relevance and review accuracy adds limited but emerging literature on online purchase intention. Marketers and policymakers will be benefited from the findings while designing and implementing different policies to attract people to persuade online purchase.